A GA for Solving a Type of Sustainable Supply Chain Design Problem - Santibanez-Gonzalez, Ernesto Del R.; Mateus, Geraldo Robson; Luna, Henrique Pacca (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2011)
We propose a hybrid genetic algorithm (GA) for solving a sustainable supply chain design problem that arises in the public sector. There is little research being done in mathematical modeling and solutions methods for these problems. The paper describes a mixed-integer 0-1 model (MIP) for this sustainable problem in which we have to determine in a network of two layers the number of facilities to be located at sites chosen from among a given set of candidate sites. Sustainable issues are integrated into the model by reducing the greenhouse gas emissions produced by the transportation and the operation of the facilities. We report computational results for instances generated from a known OR test library.